¿Paradigmas en psicología? ¿Nuevos paradigmas? (2012)
ABSTRACT: The epistemological debate in psychology is a constant throughout its history, however, in the last two decades this debate has become obsolete and few psychologists in their research deal with it, but listening to the introduction of the term paradigm, instead of running, trying to refine the reality of the problem with discipline, and magically encrypt paradigms in this reference to the solution to the real epistemological inconsistencies of its historicity, as Foucault teaches. Also touting the new complexity paradigm for psychology, little known and defined, and even offered to psychoanalysis. This work aims to make a critical overview of this picture.